Culture, Development and Adolescence – towards a Theory and History of Adolescence - Zizek, Boris (ETHICS IN PROGRESS, 2024)
The present study identifies specifics of adolescence by reconstructing the cultural-historical process of the emergence of this age, which is essentially connected to modernity, by means of two epochal works of art from the years 1719 (Daniel Defoe’s Robinson Crusoe) and 1774 (Johann Wolfgang Goethe’s Die Leiden des jungen Werthers) which are reflected upon using terms derived from development theory. This study bases its conclusions on a summary theoretical model of adolescence as the awakening of subjectivity, with critical consideration given of current tendencies in dealing with and shaping adolescence. The potential associated with this stage of life as represented amid the unleashing of modernity seems to be decreasing again in its neoliberal late phase. It seems instead to be replaced by empty stagings and conjuration of creativity.